Audiological Manifestations in Vitiligo Patients - Parvane Mahdi; Masomeh Rouzbahani; Amin Amali; Samad Rezaii Khiabanlu; Mohammad Kamali (Iranian Journal of Otorhinolaryngology, 2012)
Introduction: The hallmark of vitiligo is the disappearance of melanocytes from the skin due to an as yet unidentified mechanism. The presence of melanocytes in the auditory apparatus suggests that this system could possibly be affected by vitiligo, which targets the melanocytes of the whole body and not just the skin.The purpose of this study was to assess the incidence of auditory alterations in patients with vitiligo Materials and Methods: A total of 21 patients diagnosed with vitiligo were enrolled in this study. A group of 20 healthy subjects served as a control group. Pure tone audiometry (PTA) and measurements of auditory brain stem responses (ABR) were carried out in all participants. Results: High frequency sensory neural hearing loss was detected in 8 patients (38.09%). Analysis of ABR revealed that 10 patients (47.61%) had an abnormal increase in the latency of Wave III and 6 (28.57%) had an abnormal prolongation of the inter peak latency between Wave I and III. There was no correlation between age, duration of disease, and any of the recorded parameters. Conclusion: This study highlights the involvement of the auditory system in patients with vitiligo, suggesting that vitiligo is a systemic disease rather than a purely cutaneous problem.